If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3+5h=10+2h
We move all terms to the left:
3+5h-(10+2h)=0
We add all the numbers together, and all the variables
5h-(2h+10)+3=0
We get rid of parentheses
5h-2h-10+3=0
We add all the numbers together, and all the variables
3h-7=0
We move all terms containing h to the left, all other terms to the right
3h=7
h=7/3
h=2+1/3
| 106=p+5(2-5p) | | x-x/2-x/3=12 | | x-x/2-x3=12 | | x+2/x+3=5/ | | 6x-12=3(-2x+4) | | 5(2x-6=4(x=11) | | 15=-5(4x-7) | | n3=-17 | | -11=p+5 | | 24=5v+4 | | 4(x-9)=8(x+3 | | 5-x/3=x+2/6 | | 31=4r+11 | | 9p+9-11=-4p-2-6p | | 5.39x0.31=1.6709 | | 5x•10+10x+25x+50=185 | | (2x+4)/(3-8)=3x-2 | | 6y2+18y=0 | | 23=13+2s | | b-12=6 | | w/5-6=-7 | | 7^x+2=372 | | 60+2x=60+2(900-x) | | 40=5n+10 | | |-2x-6|=12 | | 1/3t-1/4(3t+5)=0 | | x^2+6x=x+24 | | 2/3k-(k+1/5)=1/15(k+3) | | 3/4x+2-2/5x=6 | | Y=3x+9x-30 | | a=5.7=1.5 | | 5x*3x=126 |